MENGEMBANGKAN KEMAMPUAN BERHITUNG ANAK USIA 4 – 5 TAHUN MELALUI PERMAINAN STICK ANGKA - Sukat; Arri Handayani; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Numeracy is the process or activity of carrying out mathematical operations, such as addition, subtraction, multiplication and division, in order to get the right result or answer. Counting activities involve manipulating numbers or mathematical symbols according to applicable mathematical rules. One game to improve young children's numeracy skills is the number stick game. The number stick game is an innovation in the world of educational games which aims to improve children's mathematical abilities through an interactive and fun approach. The effectiveness of number stick games can be seen from various aspects, including increasing understanding of basic mathematical concepts, developing logical thinking skills, and stimulating children's creativity. The variety of activities in this game, from number recognition to solving simple mathematical problems, provides the opportunity for children to learn in a fun and interactive way.